2012
DOI: 10.1021/jp211434f
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Modeling of the Low-Temperature Oxidation ofn-Butane: Study of the Primary Reactions

Abstract: This paper revisits the primary reactions involved in the oxidation of n-butane from low to intermediate temperatures (550-800 K) including the negative temperature coefficient (NTC) zone. A model that was automatically generated is used as a starting point and a large number of thermochemical and kinetic data are then re-estimated. The kinetic data of the isomerization of alkylperoxy radicals giving (•)QOOH radicals and the subsequent decomposition to give cyclic ethers has been calculated at the CBS-QB3 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
135
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(146 citation statements)
references
References 67 publications
(239 reference statements)
11
135
0
Order By: Relevance
“…These investigations were undertaken in light of recent experimental data detailing several intermediate species produced from the low-temperature oxidation of propane, n-butane, and n-heptane, using advanced analytical techniques. [33][34][35][36][37][38] These oxygenated intermediates include ketones, diones, and organic acids, and are formed primarily at quite low temperatures (<650 K). The reaction classes investigated were (1) show that, at 650 K, 94% of C 7 carbonyl-hydroperoxides decompose via simple fission of the O-O bond in the hydroperoxyl group.…”
Section: Additional Pathwaysmentioning
confidence: 99%
“…These investigations were undertaken in light of recent experimental data detailing several intermediate species produced from the low-temperature oxidation of propane, n-butane, and n-heptane, using advanced analytical techniques. [33][34][35][36][37][38] These oxygenated intermediates include ketones, diones, and organic acids, and are formed primarily at quite low temperatures (<650 K). The reaction classes investigated were (1) show that, at 650 K, 94% of C 7 carbonyl-hydroperoxides decompose via simple fission of the O-O bond in the hydroperoxyl group.…”
Section: Additional Pathwaysmentioning
confidence: 99%
“…In recent years, there has been a proliferation of systematic theoretical studies concerning reaction pathways of importance in the low-temperature oxidation of alkanes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . The rapid increase in the number of studies of this kind is due, in part, to more readily available computational resources.…”
Section: Introductionmentioning
confidence: 99%
“…Solid black: this work , dashed black: Villano et al . [1] , dotted black: Miyoshi [2] , dash-dot black: Wijaya et al [3] , solid grey: Cord et al [4] ,. dashed grey: Chan et al[5] , dotted grey: Goldsmith et al[6] .…”
mentioning
confidence: 99%
“…More accurate correlations have been recently proposed based on theoretical calculations (e.g. Sharma et al (2010), Cord et al (2012a)). • Formation of cyclic ethers (class 23) An example of this reaction class is shown in Fig.…”
Section: • Addition Of O 2 (Classes 11 and 26)mentioning
confidence: 99%
“…Curran et al 1998, Ranzi et al 2001, Buda et al 2005, the rate constant for this type of reaction depends only on the size of the ring which is formed. However, recent work (Cord et al 2012a) has shown the need to differentiate the type of carbon atom involved in the ring closure. The values proposed by Curran et al (1998) for the formation of furans, the types of cyclic ethers which are formed in larger amounts as shown by experiments, is k 23 , furan = 9.4 9 10 9 exp(-3.5/T) s -1 .…”
Section: • Addition Of O 2 (Classes 11 and 26)mentioning
confidence: 99%